PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK PERUSAHAAN - Lie Liana Permata Sari; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2017)
This study is aimed to examine the effect of corporate social responsibility (CSR) on corporate tax avoidance. In this research, there are independent variables used to disclosure of social responsibility, CSR and CSR Economic dimension, Social dimension. While the dependent variable, in this research is tax avoidance which was measured using the size of effective tax rates. The data of this study were taken from the manufacturing sub-sectors listed on the Indonesia Stock Exchange in 2013-2015. Study’s samples were selected by purposive sampling method; it acquired 35 companies per year that meet the criteria. This study used multiple linear regressions to examine whether CSR and CSR Economic and Social Dimensions have an influence on Corporate Tax Avoidance. The results showed that the independent variables CSR, CSR dimensions of Economy, CSR dimensions of Social that simultaneously affect the tax evasion by proxy of Effective tax rate on manufacturing sub-sectors listed in Indonesia Stock Exchange